2020
DOI: 10.1038/s41598-020-78100-z
|View full text |Cite
|
Sign up to set email alerts
|

Biomimicking properties of cellulose nanofiber under ethanol/water mixture

Abstract: The two types of cellulose nanofiber (CNF) surface characteristics were evaluated by oil contact angle under ethanol–water solution at several concentrations as well as in air. Wood pulp-based 2,2,6,6-tetramethylpiperidine-1-oxylradical (TEMPO)-oxidized cellulose nanofiber (TOCNF) sheets and bamboo-derived mechanical counter collision cellulose nanofiber (ACC-CNF) sheets were fabricated by casting followed by drying. The CNF shows underwater superoleophobic mimicking fish skin properties and slippery surface m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…CNF made from the ACC method has both hydrophobic and hydrophilic sites resulting in amphiphilic properties (Kondo et al, 2014). Halim et al (2020) demonstrated that CNF made from the ACC method was more hydrophilic than that made from the chemical method based on the contact angle measurements. Therefore, it is necessary to investigate whether the same protective effect is observed not only for the CNF made from the ACC method but also for the CNF treatment made from other methods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CNF made from the ACC method has both hydrophobic and hydrophilic sites resulting in amphiphilic properties (Kondo et al, 2014). Halim et al (2020) demonstrated that CNF made from the ACC method was more hydrophilic than that made from the chemical method based on the contact angle measurements. Therefore, it is necessary to investigate whether the same protective effect is observed not only for the CNF made from the ACC method but also for the CNF treatment made from other methods.…”
Section: Discussionmentioning
confidence: 99%
“…They demonstrated that coating a filter paper and polyethylene with CNF changed the surface property into hydrophobic and hydrophilic, respectively (Kose et al, 2011). In addition, Halim et al (2020) demonstrated that the contact angle of CNF prepared by the ACC method was smaller than that of CNF prepared by chemical treatment, suggesting that CNF made by the ACC method has higher wettability than CNF made by other methods. To investigate the potential application of CNF in agriculture, we examined whether coating with CNF protected soybean plants against P. pachyrhizi.…”
Section: Introductionmentioning
confidence: 99%
“…However, several surface properties of materials change depending on the environment especially zeta potential for cellulose-derived materials (Cheng et al, 2017a). Due to the surface of oil droplets tend to be positively charged under water environment, the repellency increases significantly to the positively charged surface such as the surface of TEMPOoxidized cellulose nanofiber (Halim et al, 2020a). Depending on the surface characteristics, three approaches (an oleophobic, hydrophobic, or Janus membrane) were applied to separate an oil-water mixture or emulsion.…”
Section: Wettabilitymentioning
confidence: 99%
“…The hydrophilicity of cellulose surfaces provides underwater oleophobicity. In nature, fish scales (Waghmare et al, 2014;Halim et al, 2020a), clamshells (Liu et al, 2012), and mussels (Wang et al, 2015d) show underwater oleophobicity. Fish keep their skin surface clean even when living in harsh environments.…”
Section: Principles Of Superoleophobic Membranesmentioning
confidence: 99%
See 1 more Smart Citation